Human-computer interaction patterns of design for multilingualism - da Rosa, Diego Moreira; Silveira, Milene (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: The increased access to computing devices and the greater connectivity among the general population, especially in developing countries, has caused the diversity of software users to expand considerably. In this context, aspects related to accessibility, cultural diversity, and multilingualism gain strength as research interests in Human-Computer Interaction (HCI). Despite that, few studies have been carried out that analyze the impact of multilingualism on interaction design strategies. Objective: In this doctoral thesis, an approach based on design patterns is adopted to analyze current design strategies aimed at the multilingualism of software users. Multilingualism is taken into consideration here in both its social form (the linguistic diversity of the user base) and its individual form (the ability of each user to understand and express themselves in different languages). Methodology or Steps: Based on a systematic review of the literature on the subject, a pattern language was composed for the design of interfaces for multilingual users. Results: The pattern language is composed of a total of 14 patterns, organized into 4 different categories that are related to different aspects of interface design: (i) language selection, (ii) presentation of multilingual content, (iii) user input in multilingual contexts, and (iv) support for language learning. All patterns are described in detail, following a standardized documentation template, and illustrated with examples from commercial applications. An initial assessment of the completeness and correctness of the language was carried out with a group of 14 students of an HCI course.